Peran Kepemimpinan dalam Meningkatkan Kinerja Pegawai pada Bidang Operasional di Pt Borneo Sentral Logistik - Fadholi, Muhammad Irfan; Fitriani, Fitriani; Rahmadania , Novita (BIMA: Jurnal Bisnis dan Manajemen, 2025)
This study aims to (1) determine the leadership role of operational employees at PT Borneo Sentral Logistik, and (2) determine the leadership roles that operational managers need to implement to improve the performance of operational employees at PT Borneo Sentral Logistik. The method used in this study was qualitative with a phenomenological approach. Data were collected through observation, interviews, and documentation with two informants. The data sources used in this study were primary data, and non-statistical data analysis techniques were used. The results of this study indicate that the current leadership role is not functioning optimally, particularly in the three main leadership roles: interpersonal, motivational, and informational roles. These roles are not being optimally implemented by operational managers. This is evident in the persistence of time discipline violations by employees, a lack of work motivation due to a lack of appreciation from superiors, and communication barriers related to information, such as the lack of clear and firm communication regarding task assignments. This has a direct impact on employee effectiveness and productivity. To overcome this problem, the leader of PT Borneo Sentral Logistik needs to improve the leadership role, especially the Interpersonal Role, the Motivating Role and the Information Provider Role in order to improve employee performance. Keywords: Leadership, Leadership Roles, Employee Performance.